2022
DOI: 10.3390/jpm12111827
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Impact of Age on Gut Microbiota in Patients with Major Depressive Disorder: A Secondary Analysis of the Prospective Observational Study

Abstract: We aimed to investigate the impact of aging on the relationship among the composition of gut microbiota, gastrointestinal (GI) symptoms, and the course of treatment for major depressive disorder (MDD) by analyzing the datasets from our previous study. Patients with MDD were recruited, and their stools were collected at three time points (baseline, midterm, and endpoint) following the usual antidepressant treatment. Gut microbiota were analyzed using 16S rRNA gene sequencing. Patients were categorized into two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In support of our finding, Li et al [ 32 ] reported an increased relative abundance of Bacteroides in insomnia patients compared with HCs; in contrast, another previous studies showed a lower proportion of Bacteroides in the insomnia group compared with HCs [ 34 , 50 ]. These discrepancies could be due to differences in the methods of genetic analysis (e.g., 16S rRNA sequencing, region, qPCR) and age of target subjects (i.e., young, middle-aged) [ 21 ]. Given that the correlation between sleep conditions and the gut microbiota remains controversial, further studies focusing on the relationship between the gut microbiota and sleep in patients with psychiatric disorders are needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In support of our finding, Li et al [ 32 ] reported an increased relative abundance of Bacteroides in insomnia patients compared with HCs; in contrast, another previous studies showed a lower proportion of Bacteroides in the insomnia group compared with HCs [ 34 , 50 ]. These discrepancies could be due to differences in the methods of genetic analysis (e.g., 16S rRNA sequencing, region, qPCR) and age of target subjects (i.e., young, middle-aged) [ 21 ]. Given that the correlation between sleep conditions and the gut microbiota remains controversial, further studies focusing on the relationship between the gut microbiota and sleep in patients with psychiatric disorders are needed.…”
Section: Discussionmentioning
confidence: 99%
“…First, the sample size of this study was small. To evaluate the more complex associations between gut microbiomes/metabolomes and sleep, and to avoid beta errors, a large cohort study would be necessary [ 14 , 20 , 21 ]. Second, we did not consider the impact of environmental factors on the composition of gut microbiota in each patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation